Urochloa decumbens grown with different Eucalyptus clones in an integrated crop-livestock-forest system - Cíntia Gonçalves Guimarães; Rosana Cristina Pereira; Karina Guimarães Ribeiro; Maria Celuta Machado Viana; José Barbosa dos Santos (Revista Ciência Agronômica)
ABSTRACT The objective of this study is to evaluate the forage mass, chemical composition, mineral content, and mineral absorption in signal grass (Urochloa decumbens) grown with different eucalypt clones in an integrated crop-livestock-forest (iCLF) system. The split-split-plot scheme included three replicates arranged in a completely randomized block design. The eucalyptus clones GG 100 and I 144 (Eucalyptus grandis × Eucalyptus urophylla) and VM 58 (Eucalyptus grandis × Eucalyptus camaldulensis) were distributed in the plots. The split plots corresponded to the growth ages of signal grass (10, 17, 24, 31, 38, 45, and 52 days after corn harvest for silage). The split-split plots corresponded to two sampling sites: center of the inter-row and soil under the Eucalyptus canopy. The Eucalyptus clones did not affect the forage mass of the grass. Forage mass was increased linearly as the grass matured and was more readily available in the center of the inter-row than under the tree canopy. The grass grown with clone I 144 presented better chemical composition, with higher levels of crude protein and phosphorus and lower levels of neutral detergent fiber. The Eucalyptus clones did not significantly affect mineral absorption. However, the Eucalyptus clones, grass age, and sampling sites significantly changed potassium absorption. It is concluded that the forage mass of signal grass is suitable for use in grazing at 38 to 52 days after corn harvest in the iCLF system in the autumn season in the Midwest region of Minas Gerais, without compromising the chemical composition of the grass.